Optimization of Solar Energy for Control Systems and Electrical Grid Projections at Substations - Permatasari, Ayunda Wulan; Fauziyah, Nur Aini; Moch.Syaifuddin; Tanjung, Riadhi Fairuz (UPN Veteran Jatim, 2025)
This research examines the utilization of solar panels as an effort to optimize solar energy in the control systems and projections of the electrical grid at substations to support the transition to renewable energy in Indonesia. Dependence on fossil fuels, which causes high carbon emissions, and Indonesia's commitment to the Paris Agreement are the main backgrounds for this innovation. The system is designed using two 12 V solar cells connected in series to produce a 24 Vdc output, and is equipped with an automatic switching mechanism between the supply from the solar panels and National Power Plant (PLN). Observations over the course of one month showed an increase in current from 0.78 A to 1.55 A and power from 18.3 W to 38.2 W, indicating an improvement in energy conversion efficiency. However, the storage capacity significantly decreased from 35.56 Ah to 7.78 Ah, due to shorter charging durations and fluctuations in ambient temperature. This system has the potential to reduce dependence on fossil fuels, support sustainable electrification, and provide environmentally friendly electricity distribution solutions in areas not yet reached by conventional networks. Further development is needed in the energy storage aspect to enhance the overall performance of the system.